A necessary and sufficient condition for the strict stationarity of a family of GARCH processes - Mika Meitz (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
We consider a family of GARCH(1,1) processes introduced in He and Teräsvirta (1999a). This family contains various popular GARCH models as special cases. A necessary and sufficient condition for the existence of a strictly stationary solution is given.
Keywords: C22; 330; GARCH; strict stationarity; Lyapunov exponent; ARCH-Modell; Ökonometrisches Modell